NON SYNDROMATIC OLIGODONTIA IN PERMANENT DENTITION: A RARE CASE REPORT - Hijazin, Reham A; Al-Shdaifat, Areej B; Sharaiha, Mais A; Jabari, Wala'a Al; Mufleh, Doaa F (Pakistan Oral & Dental Journal, 2019)
Congenital absence of teeth is the most commonly seen developmental dental anomaly in pediatric dental clinic, although agenesis of first permanent molar has the least frequency. Its prevalence in the maxilla ranges from( 0.2 to 1.5)% and in the mandible no data had been reported. The etiology of this anomaly is not exactly specified; in general it may occur in association with oligodontia or other dental disturbances. Despite the rare occurrence of first permanent molars’ agenesis, it has a significant effect on the treatment plan outcome, as it plays a major role in food mastication, vertical dimension support of the face, and anchorage of teeth against orthodontic forces. In this study we have described the clinical and radiographic findings of a rare case report among Jordanian pediatric population of congenitally missing bilateral maxillary and mandibular first permanent molars.
Keywords: Agenesis; First permanent molars; Pediatric; Anomaly; Mandibular